Kebijakan Pemerintah Indonesia dalam Menangani Kasus Eksploitasi Seksual Komersial Anak di Indonesia - Faisyal Rani; Ismandianto Ismandianto; Kirana Kirana (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
This research is motivated by the fact that the development of an increasingly modern world and the ease of transportation around the world make CSEC cases more complex. The high number of CSEC cases in Indonesia encourages the Indonesian government to focus more on developing policies and programs related to child sexual exploitation. To maximize its policies, the Indonesian government cooperates with various related parties, both government and non-government institutions, one of which is ECPAT. ECPAT is an international organization whose goal is to eliminate all forms of sexual exploitation of children. This study aims to find out the cooperation of Indonesia government policy with ECPAT in handling cases of CSEC in Indonesia. This study uses the theory of the role of International Organizations and qualitative research methods with library research techniques, namely utilizing secondary data obtained through literature studies obtained from various literatures such as books, journals, bulletins, newspapers, annual reports of several related agencies, documents, or other materials that support research. In implementing their policies, the Indonesian government and ECPAT cooperate with other parties involved in the implementation of the fight against child sexual exploitation, such as community organizations, the private sector, academics, and international agencies. The policies and programs that have been carried out by the Indonesian government with ECPAT in Indonesia are conducting research or collecting data related to child exploitation, advocating for related parties, training with related institutions to be better prepared to deal with child sexual exploitation problems, and socialization such as campaigns, workshops, or online education. Through the actions that have been taken, several achievements have been made, such as conducting research to record CSEC cases in Indonesia, such as creating a module containing ways to prevent CSEC, guiding and inviting the private sector to cooperate and be willing to pay attention to the protection of children's rights, and actively provide education and campaigns both on social media and in person.